The Influence of Maintenance Reminder Appointment and Customer Satisfaction on Customer Retention with After-Sales Service Productivity as an Intervening Variable at Auto2000 SM Raja Medan - lubis , Laila Annisyah; suryani, Wan; Rafiki , Ahmad (Amkop Management Accounting Review (AMAR), 2025)
This study examines the influence of Maintenance Reminder Appointment (MRA) and customer satisfaction on customer retention, with after-sales service productivity functioning as an intervening variable at Auto2000 SM Raja Medan. Using a quantitative explanatory design, data were collected from 371 customers through purposive sampling and analyzed using SEM-PLS. The findings indicate that MRA and customer satisfaction significantly affect service productivity and customer retention. Service productivity also significantly enhances retention and mediates both variables. These results highlight the importance of integrating proactive CRM strategies with operational efficiency to strengthen long-term customer loyalty.